2021
DOI: 10.1103/physrevlett.126.162501
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Charge-Averaged Elastic Lepton-Proton Scattering Cross Section by the OLYMPUS Experiment

Abstract: We report the first measurement of the average of the electron-proton and positron-proton elastic scattering cross sections. This lepton charge-averaged cross section is insensitive to the leading effects of hard two-photon exchange, giving more robust access to the proton's electromagnetic form factors. The cross section was extracted from data taken by the OLYMPUS experiment at DESY, in which alternating stored electron and positron beams were scattered from a windowless gaseous hydrogen target. Elastic scat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The results [16] are shown in Fig. 3, in comparison to other recent global fits of proton cross section data [23][24][25][26].…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The results [16] are shown in Fig. 3, in comparison to other recent global fits of proton cross section data [23][24][25][26].…”
Section: Resultsmentioning
confidence: 82%
“…Determining absolute cross sections was difficult for OLYMPUS, which was designed to measure cross section ratios in which the effects of acceptance, efficiency, and absolute luminosity normalization largely cancel. Nevertheless, the over-determined kinematics in elastic scattering The charge-averaged cross section as measured by OLYMPUS [16], compared to other recent proton form-factor predictions [23][24][25][26]. A normalization uncertainty of ±7.5% is not shown.…”
Section: Charge-averaged Cross Section Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…One of these recent experiments, OLYMPUS, has recently published absolute cross sections for both electron and positron elastic scattering [14]. The average of the two-the lepton charge averaged cross section-has the convenient feature of being insensitive to two-photon exchange effects at lowest order.…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth review can be found in [3]. Previous measurements [4,5] observed a small (∼1%) "hard" two-photon exchange contribution but were limited to relatively low Q 2 (< 2.1 (GeV/c) 2 ) where the proton form factor discrepancy is not clear. TPEX would make measurements at Q 2 up to 4.6 (GeV/c) 2 where the discrepancy is more obvious.…”
mentioning
confidence: 99%